The (Un)Making of a History Book: Revisiting the Earliest Manuscripts of Eadmer of Canterbury's Historia novorum in Anglia. (18th September 2019) - Pohl, Benjamin
Abstract: This article revisits the earliest manuscripts of the 'History of Recent Events in England' ( Historia novorum in Anglia ) written by Eadmer of Canterbury during the first decades of the twelfth century. Today, it is widely recognised as one of the most important pieces of historical writing produced in England during the period following the Norman Conquest. The article is the first in over twenty years to offer an in-depth codicological study of the Historia novorum's principal manuscripts, and it provides a critical corrective to the canonical studies of Richard Southern (1963/90), whose arguments still form the communis opinio in present-day scholarship. Analysis shows that, contrary to established scholarly consensus, Eadmer did not compose his work in two distinct versions separated by a five-year writing hiatus, but that he kept writing continuously and produced one or more interim redactions of the Historia novorum that continued the narrative up to key moments in the history of early twelfth-century England.